3-6 yaş döneminde çocuklara sahip anne babaların cinsel gelişim ve eğitim hakkındaki bilgi düzeyleri ve tutumları - Baysan, Medine Pervin (İstanbul Medipol Üniversitesi Sağlık Bilimleri Enstitüsü, 2020)
Bu çalışma 3-6 yaşında çocuğa sahip olan ailelerin çocuk cinsel gelişimi hakkındaki bilgi düzeyleri ve tutumlarını belirlemek amacıyla yapılmıştır. Çalışma 3-6 yaşında çocuğu olan 102 anne 18 baba olmak üzere toplam 120 ebeveyn ile yürütülmüştür. Çalışmada araştırmacı tarafından oluşturulmuş "Ailelere Yönelik Çocuk Cinsel Gelişim ve Eğitimi Bilgi ve Tutum Formu" kullanılmıştır. Form oluşturulduktan sonra uzman görüşü alınmıştır. Pilot çalışma yapılarak sorular düzenlenmiştir. Verilerin analizinde tanımlayıcı istatistik, T Testi, Anova, Crosstab ve Ki kare testleri kullanılmıştır. Ebeveynler, genellikle çocuklarının cinsellikle ilgili sorularına verecek cevabı bulma konusunda güçlük yaşadıklarını belirtmiştir. Babaların annelere oranla çocukların cinsellikle ilgili soruları karşısında daha fazla tedirgin olma, sorulardan kaçınma, konuyu değiştirme, çocuğuna soru sormaması gerektiğini belirtme vb. davranışlarda bulunduğu ortaya çıkmıştır. Çocuklara cinsel eğitimin kimin tarafından verilmesi gerektiği sorusuna en çok anneler cevabının verildiği (%36,2), babaların %93,8'inin cinsel eğitimi annenin vermesi gerektiğini düşündüğü bulunmuştur. Ebeveynlerin %79,7'sinin çocuk cinsel eğitimi başlama zamanını yanlış bildiği, cinsel eğitimin çoğunlukla çocukları cinsel istismardan koruma olarak düşünüldüğü, annelerin babalardan daha fazla çocuk cinsel gelişimiyle ilgili bilgiye sahip olduğu görülmüştür. Ebeveynlerin %68,9'unun çocuk cinsel gelişim eğitimi almak istediği, çocuk cinsel gelişimi eğitimi alanların bilgi düzeyinin eğitim almayan ebeveynlere göre anlamlı şekilde fazla olduğu bulunmuştur. Ebeveynin eğitim durumu, kendini algıladığı sosyo-ekonomik düzey ile bilgi düzeyi arasında anlamlı bir farklılık bulunmamıştır. Sonuç olarak ailelerin çocukların cinsellikle ilgili sorularına karşı yaşadıkları endişelerin genellikle nasıl cevap vereceklerini bilmemelerinden kaynaklandığı, cinsel gelişim bilgi düzeylerinin eksik olduğu, ailelerin eğitime ihtiyacının olduğu görülmüştür. Ailelere verilen cinsel eğitimin, çocuğa verilen olumsuz tepkileri azaltacağı ve çocukların sağlıklı cinsel kimlik gelişimini sağlayacağı düşünülmektedir.

This research was conducted to identify parent's, whose children's age is between the age of 3- 6, knowledge and attitude about children's sexual development. In this research, it was worked with 120 parents whose children's age is between 3 and 6. Out of 120 parents, 102 of them are mothers and 18 of them are fathers. In the research, "Knowledge and Attitude Form for Families on Child Sexual Development and Education" was used which was formed by researchers. It was taken expert opinion after form was formed and questions were formed by doing pilot study. It was used descriptive statistics, T test, Anova, Crosstab and Ki kare (kareyi ingilizce istersen square yaz) tests for data analysis. Parents stated that they were having hard time to answer the questions of their children about sexuality. It was observed that compared to their partners, fathers are having harder time and being more anxious to answer children's questions about sexuality. Also it was seen that they tend to avoid questions, change the subject and tell the kid to not ask that kind of questions compared to mothers. When it was asked who should educate children about sexuality, it was seen that popular answer is mothers (%36,2). It was also found that 93,8% of fathers think that sexuality education should be given by mothers. Moreover, it was found that 79,7% of parents have wrong idea about beginning time of child sexual development and think that sexual education is just for to prevent children from sexual harrasment. It was seen that mothers have more idea than fathers about child sexual development. 68,9% of parents stated that they would want to join a course about child sexual development. It was seen that parents who take the course about this subject have more information about child sexual development. It was seen that there is no meaningful difference between parent's education level, socio economical status and knowledge level. As a result, it was seen that parent's anxiety about answering their children's questions about sexuality stems from the fact that they don't know what to say. It was observed that knowledge level of child sexual development is incomplete and parents need to have an education about that. It was thought that child sexual development education enables to decrease negative reactions towards children about the subject and provides children to have a healthy sexual identity development.
Knowledge level and attitudes of parents whose children's age is between 3 and 6 about chi?ld sexual development and educati?on
Keywords: Cinsellik; Cinsel Gelişim; Cinsel Eğitim; Çocuk Gelişimi; Sexuality; Sexuality Development; Sexuality Education; Child Development